THE GENETIC CURE FOR BLINDNESS: ADVANCES IN RETINAL THERAPY (Journal of Medical & Health Sciences Review, 2025)
Background: Gene therapy involves the transfer of genetic material to specific tissues or organs to achieve therapeutic effects, aiming to correct genetic abnormalities or diseases. This method utilizes cells as biological vehicles to deliver the therapeutic genes. Eye diseases, particularly those affecting the retina, have a significant hereditary component, which has prompted research into gene therapy as a potential treatment option. Macular diseases and retinal dystrophies, due to their genetic nature, are increasingly being targeted by innovative therapeutic strategies, including gene therapy.Objective: The objective of this review is to explore the concept of gene therapy, the different types of vectors used for gene delivery, and the potential of gene therapy in treating retinal dystrophies.Methods: This paper examines various studies, clinical trials, and scientific literature to assess the current advancements in gene therapy for retinal diseases. It will also discuss the types of gene therapy vectors, such as viral and non-viral vectors, that are used for efficient gene delivery in the eye.Results: Gene therapy has emerged as a promising approach for the treatment of retinal dystrophies. Advancements in vector design and gene delivery methods have significantly improved the potential effectiveness of gene therapy. Studies have shown that gene therapy can potentially slow or halt the progression of retinal dystrophies by correcting genetic defects at the cellular level.Conclusion: Gene therapy holds considerable promise as a treatment for retinal dystrophies, with ongoing research and clinical trials highlighting its potential. The choice of vector type plays a critical role in the success of gene therapy, and future research is necessary to refine these methods to maximize their therapeutic benefits for patients suffering from inherited retinal diseases.